THE EFFECT OF MICROBES ISOLATED FROM THE FEMALE REPRODUCTIVE TRACT OF PREGNANT WOMEN ON FETUSES - Radhi, Zahraa Essa; Al-Saadi, Dania Ali Azeiz; Alhachem, Hind Fieq Abdalameer; Al-Khafaji , Zainab Abdul Jabbar; Harjan, Qusay Jabbar (PT. Antis International Publisher, 2025)
Objective: This study explores the role of microorganisms isolated from the female reproductive tract during pregnancy and their potential impact on fetal development and pregnancy complications. Method: A descriptive, literature-based approach was employed to analyze microbial populations across various anatomical sites—vaginal, cervical, endometrial, tubal, and ovarian—focusing on their interactions with the maternal immune system and reproductive outcomes. Results: The findings reveal that microbial imbalance, particularly the reduction of Lactobacillus species, disrupts immune regulation and compromises epithelial integrity, leading to adverse outcomes such as premature labor, miscarriage, infections, and congenital abnormalities. Pathogens including Candida, Trichomonas, Cytomegalovirus, and Group B Streptococcus were identified as major contributors to these complications. Novelty: Unlike prior studies that often examine isolated reproductive sites, this research integrates microbiome data from both upper and lower reproductive tracts, offering a comprehensive view of organ-specific dysbiosis and its influence on maternal-fetal health. These insights suggest new directions for preventive strategies, targeted therapies, and the development of biomarkers aimed at restoring microbial equilibrium to safeguard pregnancy outcomes.